Progranulin promotes osteogenic differentiation of periodontal membrane stem cells in both inflammatory and non-inflammatory conditions. Issue 8 (August 2021) - Yu, Miao; Sun, Long; Ba, Pengfei; Li, Linxia; Chen, Jing; Sun, Qinfeng
Objective: The growth factor progranulin (PGRN) is widely expressed and plays important roles in anti-inflammatory signaling and bone regeneration. However, the anti-inflammatory and pro-osteogenic roles of PGRN in periodontitis are seldom studied. We used an in vitro model to investigate whether PGRN can promote osteogenic differentiation of periodontal ligament stem cells (PDLSCs). Methods: PDLSCs were treated with PGRN (0 to 100 ng/mL) and the optimal concentrations required to induce proliferation and osteogenesis were identified. PDLSCs were cultured with 10 ng/mL tumor necrosis factor (TNF)-α, 25 ng/mL PGRN, or 10 ng/mL TNF-α + 25 ng/ml PGRN; untreated PDLSCs were used as controls. The effects of PGRN on PDLSC proliferation and osteogenic differentiation were assessed. Results: PGRN (5, 25, and 50 ng/mL) promoted PDLSC proliferation and osteogenic differentiation, with the 25-ng/mL dose showing the largest effect. Furthermore, 25 ng/mL PGRN reversed inhibition of osteogenic differentiation by TNF-α. Conclusion: PGRN promotes PDLSC proliferation, osteogenic differentiation, and mineralization in both inflammatory and non-inflammatory conditions. The 25-ng/mL PRGN dose was the most suitable for inducing proliferation and osteogenesis. Further studies using animal models will be required to obtain pre-clinical evidence to support using PGRN as a treatment for periodontitis.